Vocational and Technical Education in Nigeria: Issues, Challenges and the Way Forward - A.E.B, Ubom; ., Aregbesola B.G. (Journal of Education and Vocational Research, 2013)
The paper seeks to look into the subject of vocational and technical education in Nigeria the issues involved, challenges encountered and how it can get better. The purpose is to unveil education as an instrument for transformation, productivity and motivator for the betterment of individual who has passed through it. In this paper vocational and technical education can be seen as that aspect of education use to gear the preparation of skilled manpower towards nation’s development. Major constraints to vocational education such as nation’s growth and vocational technical education, job scarcity and severance of Nigerian youths, implication of technology on vocational education training, parental attitudes toward vocational education, vocational for secondary schools, vocational technology elucidation for present needs and redundancy expiration & engagement with vocational technical education were discussed. The paper concluded that Nigerians should give vocational technical education leverage in her educational system and some recommendations were proffered.